Teachers’ Strategies in Teaching English Vocabulary to Tenth-Grade Students at SMKN 1 Tapaktuan in the Academic Year 2024/2025 - Yulita Halim (Indo Publishing, 2026)
The present study sets out to explore and analyze the instructional strategies employed by English teachers in teaching vocabulary to tenth-grade students at SMKN 1 Tapaktuan during the 2024/2025 academic year. Vocabulary acquisition is widely recognized as a cornerstone of language learning, and teachers’ choices of strategies significantly shape learners’ success. This research not only identifies the specific strategies used but also examines the contextual and pedagogical factors that influence teachers’ decisions. By doing so, it aims to provide a comprehensive understanding of how vocabulary instruction is managed in a vocational high school setting, where students often face unique challenges compared to those in general academic tracks. The study adopts a qualitative descriptive design, which is particularly suited to capturing the richness and complexity of classroom practices. Unlike quantitative approaches that focus on numerical data, qualitative research emphasizes meaning, interpretation, and context. In this case, the voices and experiences of teachers are central. Two English teachers were selected as the primary subjects, allowing for an in-depth exploration of their perspectives and practices. Data collection relied on semi-structured interviews, which provided flexibility for teachers to elaborate on their experiences while ensuring that key topics were consistently addressed. In addition, documentation such as lesson plans and syllabi was analyzed to triangulate findings and provide evidence of how strategies were planned and implemented. The analytical framework was guided by Miles and Huberman’s model of qualitative data analysis, which involves three interconnected steps: data reduction, data display, and conclusion verification (Sugiyono, 2015). Data reduction refers to the process of selecting, simplifying, and focusing on the most relevant information. Data display involves organizing information in a way that makes patterns and relationships visible. Finally, conclusion verification ensures that interpretations are credible and supported by evidence. This systematic approach allowed the researchers to move beyond surface-level descriptions and develop well-grounded insights into vocabulary teaching practices.